2017
DOI: 10.2147/ndt.s146152
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical assessments of thyroid profile, serum 25-hydroxycholecalciferol and cluster of differentiation 5 expression levels among children with autism

Abstract: BackgroundThe exact pathogenesis of autism is still unknown. Both thyroid hormones and 25(OH)D are important for brain development, in addition to CD5; all have immunomodulatory actions by which their dysregulation may have a potential role in autism pathogenesis.ObjectivesThe objectives of this study were to assess the thyroid profile, serum 25(OH)D levels and CD5 expression levels among autistic patients and to find out the correlations between the measured biomarkers with each other on one side and with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 26 publications
1
15
0
1
Order By: Relevance
“…This fat-soluble vitamin has important immunomodulatory and neuroprotective functions (Aranow, 2011 ; Wrzosek et al, 2013 ), and deficiency may be contributing to immune and behavioral abnormalities in people with ASD. Daily supplementation with Vitamin D, not to exceed 5,000 IU/day, was found to significantly improve behavioral outcomes and lowered elevation of CD5 expression in children with ASD, supporting a role for Vitamin D in modulating the immune system (Desoky et al, 2017 ; Feng et al, 2017 ; Saad et al, 2018 ). As previously discussed, children with ASD have altered T cell profiles, perhaps due to altered transcriptional activity (Ahmad et al, 2017b ).…”
Section: Improvement Of Symptoms With the Use Of Immune-modulating Drmentioning
confidence: 84%
See 1 more Smart Citation
“…This fat-soluble vitamin has important immunomodulatory and neuroprotective functions (Aranow, 2011 ; Wrzosek et al, 2013 ), and deficiency may be contributing to immune and behavioral abnormalities in people with ASD. Daily supplementation with Vitamin D, not to exceed 5,000 IU/day, was found to significantly improve behavioral outcomes and lowered elevation of CD5 expression in children with ASD, supporting a role for Vitamin D in modulating the immune system (Desoky et al, 2017 ; Feng et al, 2017 ; Saad et al, 2018 ). As previously discussed, children with ASD have altered T cell profiles, perhaps due to altered transcriptional activity (Ahmad et al, 2017b ).…”
Section: Improvement Of Symptoms With the Use Of Immune-modulating Drmentioning
confidence: 84%
“…Nutritional or supplemental approaches may be helpful in modulating immune function in people with ASD. Several studies have found children with ASD to be deficient in serum levels of vitamin D (25-hydroxycholecalciferol), and serum levels were found to be negatively associated with language and behavioral scores on the ABC and the Childhood Autism Rating Scale (CARS) (Desoky et al, 2017 ; Saad et al, 2018 ), (Feng et al, 2017 ). Serum vitamin D levels also negatively correlated with the presence of anti-myelin-associated glycoprotein autoantibodies (Mostafa and Al-Ayadhi, 2012a ).…”
Section: Improvement Of Symptoms With the Use Of Immune-modulating Drmentioning
confidence: 99%
“…This result speaks against a peripherally maintained B-cell immune process and suggests that we need more careful pathophysiological studies. 89 Dietary intervention with Vit.D is based on a supposed, but not always confirmed, 79,90 Vit.D deficiency in the serum of children with ASD, and on the fact that the level of Vit.D is inversely correlated with language and behavioural scores on Childhood Autism Rating Scale. 91 Vit.D has immunomodulatory and neuroprotective functions, particularly during pregnancy; its serum shortfall may therefore contribute to the persistence of both immune and behavioural abnormalities in post-gestational age.…”
Section: Postnatal Intervention In Humansmentioning
confidence: 99%
“…All patients were subjected to a thorough clinical history, including developmental history and a detailed history of the presenting symptoms. Individual interviews with every included child and his/her parents were conducted to clinically assess the severity of their autistic symptomatology using the Childhood Autism Rating Scale (CARS) as described in previously published works 24,25 with total scores of 30 or above strongly suggest autism diagnosis, 30-36 have mild to moderate autism, 37-60 suggest severe autism. 26 The questionnaires were administrated by two well-trained and experienced clinical psychologists.…”
Section: Data Collections Clinical Evaluation Of the Included Patientsmentioning
confidence: 99%